A town overshadoved by a museum: Problems of tourism development in Oświęcim - Kruczek, Zygmunt; Nowak, Agnieszka (Turyzm/Tourism, 2019)
The article presents issues of tourism development in Oświęcim – a town that remains in the shadow of the former genocide site of Auschwitz-Birkenau Concentration Camp. The authors’ aim is to present the results of research on the image of the town, as well as activities leading to a change of the unfavourable image of Oświęcim: “a town overshadowed by a museum”. They are included in “The Strategy for Tourism Development in Oświęcim, 2018-2030”, developed with the support of the authors of this article. The paper also presents an analysis of tourism development and tourist assets with respect to using them to create a supplementary offer for tourists visiting the Auschwitz-Birkenau Memorial and Museum.